Jurnal pendidikan : teori, penelitian, dan pengembangan - Universitas Negeri Malang. Pascasarjana (Graduate School of Universitas Negeri Malang, 2016)
Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan (Education Journal: Theory, Research, and Development) is an electronic journal focused on scientific articles concerning education issues in general, published by Graduate School of Universitas Negeri Malang since January 2016.
Keywords: Education : Periodicals; Education : Indonesia : Periodicals; Education; Indonesia